Impact of Resident Involvement on 30-Day Postoperative Outcomes in Orthopedic Shoulder Surgery - Aaron J. Marcel; Richard S. Feinn; Karen M. Myrick (Advances in Orthopedics)
The literature concerning resident involvement in shoulder surgery is limited. The purpose of this study was to examine whether resident involvement across all orthopedic shoulder surgeries is associated with adverse 30-day outcomes. Utilizing the American College of Surgeons National Surgical Quality Improvement Program database, patients who underwent shoulder surgery with or without a resident present were analyzed. Independent t-test and chi-square or Fischer’s exact test were used appropriately. A logistic regression model was used to calculate adjusted odds ratios. This study examined 5,648 patients: 3,455 patients in the “Attending alone” group and 2,193 in the “Attending and resident in the operating room” group. Resident presence in the operating room was not associated with increased complications, except for bleeding transfusions (OR 1.71, CI 1.32–2.21, P≤0.001). This study demonstrates that resident involvement in orthopedic shoulder surgery does not present an increased risk for 30-day complications when compared to surgeries performed with the attending surgeon alone.